Armies of Julius Caesar 58-44 BC - D'Amato, Raffaele 1964- (Bloomsbury Publishing Plc, 2021)
Cover -- Contents -- Introduction -- Chronology (BC) -- Organization Of The Consular Army -- Legiones -- Caesar's legionarii -- Equites -- Caesar's bodyguards -- Command Structure -- Legati -- Praefecti -- Quaestores -- Tribuni and contubernales -- Centuriones -- Other 'non-commissioned' officers -- Socii auxiliaries -- Elephants -- Arms &amp -- Equipment -- Shafted weapons: the pilum, gaesum and hasta -- Swords -- Daggers -- Belts -- Helmets -- Types -- Details -- Body Protection -- Ringmail -- Organic armours, and under-armour garments -- Metallic armours -- Shields -- The scutum -- The clipeus -- Equipment Of Socii Auxiliaries -- Germanics -- Celts -- Balearics -- Cretans -- Iberians -- Greeks -- Other Equipment -- Standards -- Musical instruments -- Cavalry equipment -- Clothing -- Bibliography -- Index -- Imprint